EVALUASI KINERJA EMBUNG SONG BOLONG SELOPAMIORO IMOGIRI, BANTUL - Muchamad Arif Budiyanto; Agung Prasetyo (Fakultas Teknik Universitas Cokroaminoto Yogyakarta, 2020)
Small dam is a water storage system, which is usually used by residents in areas with limited water resources. Construction of small dam Song Bolong as one of the water storage is expected to be used to increase agricultural products in the area of small dam Song Bolong. This study intends to determine the optimization of the use of small dam Song Bolong in order to know the area of land that can be rised by the water availability of small dam Song Bolong. This study uses the software that is in Ms. Excel as a tool in optimization analysis. The optimization Model used is monthly optimization on MT I, MT II and MT III. The goal function is the maximum yield of the small dam Song Bolong to meet the need for irrigation water. While obstacle functions include the magnitude of available discharge, the volume of the reservoir and the available land area. Based on the results of the optimization, the water potential in small dam Song Bolong provides maximum planting intensity with rice planting pattern system (Mt I) – Palawija (Mt II) – Palawija (Mt III), at the beginning of January period 1 planting, which shows the planting intensity occurs by 168% for one year. At MT I The planting intensity is 140%. At MT II The planting intensity is 20%. As for MT III the planting intensity is 8%.